Interaction of antiphospholipid antibodies with endothelial cells in antiphospholipid syndrome - Feng, Weimin; Qiao, Jiao; Tan, Yuan; Liu, Qi; Wang, Qingchen; Yang, Boxin; Yang, Shuo; Cui, Liyan (Frontiers in Immunology, 2024)
Antiphospholipid syndrome (APS) is an autoimmune disease with arteriovenous thrombosis and recurrent miscarriages as the main clinical manifestations. Due to the complexity of its mechanisms and the diversity of its manifestations, its diagnosis and treatment remain challenging issues.Antiphospholipid antibodies (aPL) not only serve as crucial "biomarkers" in diagnosing APS but also act as the "culprits" of the disease. Endothelial cells (ECs), as one of the core target cells of aPL, bridge the gap between the molecular level of these antibodies and the tissue and organ level of pathological changes. A more in-depth exploration of the relationship between ECs and the pathogenesis of APS holds the potential for significant advancements in the precise diagnosis, classification, and therapy of APS. Many researchers have highlighted the vital involvement of ECs in APS and the underlying mechanisms governing their functionality. Through extensive in vitro and in vivo experiments, they have identified multiple aPL receptors on the EC membrane and various intracellular pathways. This article furnishes a comprehensive overview and summary of these receptors and signaling pathways, offering prospective targets for APS therapy.